Theoretical bases of education of cross-cultural values ​​in youth (Pedagogy of Higher and Secondary Education, 2022)
The article analyzes the theoretical basis of training cross-cultural values in youth. Consider key approaches and guidelines of modern cross-cultural education.
Keywords: cross-cultural values; intercultural relations; cultural environment